GM-003 Evaluation of the effectiveness of a basic training course: the process of pharmaceutical logistics, prospects and challenges for the national health service. (24th March 2015) - Coppolino, S; Pani, M; Adami, S; Bartolini, F; Tommasi, M; Turchetti, G
Abstract : Background: The growth of healthcare spending and the concurrent gradual reduction of resources require interventions oriented to the reorganisation of drugs supply chain and medical devices in the various steps from the manufacturer to the bed of the patient and/or his house. Logistics and innovation of hospitals and territorial structures thus possess a key role in increasing the efficiency and quality of health services. Purpose: The purpose of this study is to evaluate satisfaction and effectiveness of a basic training program about pharmaceutical logistic processes organised and held from the Logistic SIFO Area (LSA). Material and methods: During the period starting from February to April 2014 there were three training sessions (Catania, Torino, Pisa) lasting thirteen hours with a total of 70 participants. By administrating a course satisfaction questionnaire and an evaluation of the belonging structure it was possible to characterise both the course participants and the ability to transfer what they have learnt in their working contexts. The responses, assessed anonymously, were processed statistically. Results: 70 satisfaction and 60 self-assessment questionnaires were analysed. 52% of participants judged as "highly important" all topics treated and 50% rated as "very important" the educational quality of the course. The analysis of the questionnaire for the performance assessment showed that participation in the course increased by 70% in the learners' willingness to improve their organisational system and raised awareness in the need for performance investigation analysis tools, new technologies, constraints given by the Regional Administration and LHA. 60% of participants found organisational barriers in the modification of the current pharmaceutical logistics paths. Conclusion: Obtained data allowed us to verify the effectiveness of the methodology adopted by the LSA dealing with issues relevant to the profession, as well as highlighting both the utility to carry out further editions of the Basic Course and to develop an Advanced Course. References and/or acknowledgements: None No conflict of interest.